Gain Enhancement of a Traditional Horn Antenna using 3D Printed Square-Shaped Multi-layer Dielectric Lens for X-band Applications - Aysu Belen; Peyman Mahouti; Filiz Güneş; Özlem Tari, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this work, gain of a traditional horn antenna is enhanced up to 2.9 dB over X-band using 3D printed square-shaped multi-layer lens. For this purpose, firstly the multi-layer lenses are designed using Invasive Weed Optimization (IWO) and simulated in 3-D CST Microwave Studio (MWS) environment as consisting of square-shaped five layers with variable dielectric constants and heights. Thus, optimum values of the dielectric constants and heights are resulted limiting from 1.15 to 2.1 and 9.2 mm to 10 mm, respectively compatible for Fused Deposition Modeling (FDM) based 3D-printing process. Finally, the optimum lens is realized by 3D printer via FDM evaluating infill rate of cheap Polylactic Acid (PLA) material for each layer. The simulated and measured performance of the multi-layer dielectric structures are hand to hand. The horn antenna equipped by our proposed dielectric lens achieves gain enhancement of the traditional antenna up to 2.9 dB over the operation band. Furthermore, the proposed design is compared with the counterpart designs in literature and based on the comparison results it can be said that the proposed design achieves the better performance in the smaller in size as equipped a traditional X-band horn antenna.